Unified Fractional Derivative Formulae for the Multivariable Aleph-Function (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: general class of multivariable polynomial; saigo-maeda operator; multivariable aleph-function; multivariable H-function; alephfunction; fractional der